Public and Engaged Anthropology: The Legacy of Nina S. de Friedemann - Friedemann-Sánchez, Greta (Journal of Leadership, Accountability and Ethics, 2023)
Nina S. de Friedemann (1930-1998) was a public anthropologist. She practiced engaged research, with a view to promoting social justice for the communities with whom she collaborated and studied, and she anticipated the public anthropology of the North Atlantic academia by five decades. A pioneer in AfroColombian studies and in visual anthropology, she documented and defended the cultural contributions of Black populations to the identity of an ethnically diverse Colombia. Friedemann’s fundamental work inspired leaders of the Black communities in their demands that culminated in Law 70 of 1993, also known as the ley de negritudes. Her research materials are housed at the Luis Angel Arango Library under the name Fondo Nina S. de Friedemann, a repository available for study. Using unpublished materials, correspondence, publications, and photographs, Greta Friedemann-Sánchez reflected on three pillars of her mother’s ethical legacy within the contemporary normative framework for the protection of human subjects and the historical context during which Nina S. de Friedemann worked as an anthropologist.